Polysaccharides and lignin from oak wood used in cooperage: Composition, interest, assays: A review - Le Floch, Alexandra; Jourdes, Michael; Teissedre, Pierre-Louis (Carbohydrate research, 2015)
•The choice of raw material determines oak wood barrels quality.•The barrels or alternative fabrication processes can modify oak wood composition.•Oak wood macromolecules (polysaccharides, ellagitanins) have a sensorial interest. It is widely accepted that alcoholic beverage quality depends on their ageing in premium quality oak wood. From the choice of wood to beverage ageing, through the different steps in cask manufacturing, many factors should be considered. One of the biggest challenge in cooperages is to take into account all these factors. Most of the studies are interested in phenolic compounds, extracted during ageing and especially involved in wine oxidation, colour, and sensory properties such as astringency and bitterness. Oak aroma volatile compounds have also been the subject of numerous studies. These compounds of interest are part of low molecular weight compounds which represent 2%–10% of oak wood composition. However, three polymers constitute the main part of oak wood: cellulose, hemicellulose and lignin. As far as we are aware, few studies concerning the role of these major macromolecules in oak wood have been published previously. This article reviews oak wood polysaccharides and lignin, their potential interest and different assays used to determine their content.